Changing Traditions in Non-fictional Jewish-Canadian Writing – the Study of Selected Texts by Eva Hoffman, Elaine Kalman Naves and Bernice Eisenstein - Drewniak, Dagmara (My University, 2014)
Recent years have witnessed a substantial growth of interest in various forms of non-fictional writing. Canadian literature has also abounded in a range of non-fictional texts. Among the different forms of such texts are memoirs and life narratives. This paper aims at tracing the changes within formal trends and tendencies in these narratives. Therefore, the article offers an examination of a selection of non-fictional texts from the perspective of paratextual elements such as photographs, maps, drawings, illustrations, ekphrasis and other graphic aspects as well as metatextual, self-conscious remarks on the process of writing included in the texts. The texts chosen for analysis are written by contemporary Canadian authors of Jewish origins (or authors identified with Canada and more broadly with North America as it is in Eva Hoffman’s case). The authors of the chosen memoirs are all first or second generation immigrants whose experiences of migration, changing countries and cultures have shaped their identities formed through their own or inherited post/memories. Family histories combined with personal accounts can be found in all selected texts such as: Eva Hoffman’s seminal “Lost in Translation” (1989) a text partly devoted to her Canadian experiences, Elaine Kalman Naves’ “Journey to Vaja. Reconstructing the World of a Hungarian-Jewish Family” (1996) and “Shoshanna’s Story. A Mother, a Daughter, and the Shadows of History” (2003), as well as Bernice Eisenstein’s “I Was a Child of Holocaust Survivors” (2006) which is one of the first graphic memoir in Canadian life writing. All of these texts were published in Canada within the last few decades (it needs to be noted that it is only Eva Hoffman’s book that is available in Polish) and they all take up a discussion concerning the problem of immigrant identity and offer a range of paratextual and metatextual remarks whose appearance contributes to the inquiry into the contemporary developments in Jewish-Canadian life writing.
Keywords: Jewish-Canadian literature; life writing; Eva Hoffman; Elaine Kalman Naves; Bernice Eisenstein